1988
DOI: 10.1007/bf00195368
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone in combination with prednimustine in treatment of unfavorable non-Hodgkin lymphoma

Abstract: Mitoxantrone (Novantrone) and prednimustine (Sterecyt) are both active as single agents in the treatment of unfavorable non-Hodgkin lymphoma (UNHL). The efficacy and toxicity of the combination of these agents (NOSTE) was evaluated in 28 patients with advanced histopathologically proven UNHL who were not eligible for aggressive conventional chemotherapy. The median age was 68, range 45-84. Sixteen patients were previously untreated. Eleven patients had received doxorubicin or epidoxorubicin containing regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It was derived from the combination of prednimustine and mitoxantrone (PmM), which was introduced by Landys in 1988, who reported a high remission rate in patients with recurrent and untreated, indolent lymphomas. 13 A subsequent trial by the German LowGrade Lymphoma Study Group (GLSG) confirmed those data and also showed significantly greater antilymphoma activity and a more favorable toxicity profile for PmM when it was compared randomly with cyclophosphamide, vincristine, and prednisone (COP). 14 When prednimustine, which is an ester of chlorambucil and prednisone, was taken off of the market because of a high rate of secondary acute myeloid leukemias and myelodysplastic syndromes, chlorambucil and prednisone were used as separate agents.…”
mentioning
confidence: 87%
“…It was derived from the combination of prednimustine and mitoxantrone (PmM), which was introduced by Landys in 1988, who reported a high remission rate in patients with recurrent and untreated, indolent lymphomas. 13 A subsequent trial by the German LowGrade Lymphoma Study Group (GLSG) confirmed those data and also showed significantly greater antilymphoma activity and a more favorable toxicity profile for PmM when it was compared randomly with cyclophosphamide, vincristine, and prednisone (COP). 14 When prednimustine, which is an ester of chlorambucil and prednisone, was taken off of the market because of a high rate of secondary acute myeloid leukemias and myelodysplastic syndromes, chlorambucil and prednisone were used as separate agents.…”
mentioning
confidence: 87%
“…To our knowledge, no results from the combination of mitoxantrone, chlorambucil and prednisone (MCP), which has widely been applied in various other types of indolent lymphomas [15][16][17][18], have been reported in patients with MALT lymphoma. In view of the fact that chlorambucil is already an effective and frequently used treatment option in MALT lymphomas [13,[19][20][21] and mitoxantrone shows high activity in the treatment of indolent lymphoma [15,16,18], this combination appears to be an attractive treatment option. We have therefore performed a retrospective analysis of our results with MCP in the therapy of patients with MALT lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistologic marker studies of the biopsy specimen revealed a B-ecll phenotype. After ini tiating acute hemodialysis we consequently treated our patient with 2 mg of vincristine on day l and 100 mg of prednisone for 5 days followed l week later by a more aggressive chemotherapy regimen [4] consisting of prednimustine and mitoxantronc (PmM protocol). According to the age of our patient, we reduced mitoxantronc to 8 mg/m2 on day l. while the prednimustine dosage was 100 mg/m2 on days l-5 every 4 weeks for 3 cycles.…”
Section: Kargermentioning
confidence: 99%